Denudation intensity and control in the Chinese Tian Shan: new constraints from mass balance on catchment‐alluvial fan systems. Issue 8 (18th January 2016) - Guerit, Laure; Barrier, Laurie; Jolivet, Marc; Fu, Bihong; Métivier, François
Abstract: Tectonics and climate are usually seen as the main controlling factors of denudation rates, which seem to rise with the tectonic activity and to decrease when the climate becomes drier. However, the low denudation rates observed in semi‐arid to arid contexts are generally measured on orogenic plateaus where the respective influence of the flat relief and the dry climate cannot really be unravelled. The Chinese Tian Shan was chosen as a case study. In the northern piedmont of this mountain range, a series of well‐preserved Quaternary alluvial fans offer the opportunity to perform a mass balance study at the scale of several catchment areas and several hundreds of thousands of years. Based on a geometrical reconstruction of these fans, the volumes of sediments exported out of 10 drainage basins during the Middle–Late Pleistocene (from ∼300 to ∼12 kyr) and the Holocene (from ∼12 kyr to present) have been estimated. From these volumes, an average denudation rate of ∼135 m/Myr was determined in the Tian Shan Range for the last 300 kyr. In agreement with other mass balances performed in the same area, the typical denudation intensity of the northern Tian Shan is thus of a few hundred meters per million years at most, regardless of the space and time scales considered. From a comparison with denudation rates in other mountain ranges throughout the world, we suggest that a dry climate can dramatically limit the denudation intensity even in active orogenic systems with a high topographic gradient like the Tian Shan. As a result, the time required to reach equilibrium between denudation and rock uplift in these systems could be extremely long (i.e. of more than several million years). Copyright © 2016 John Wiley & Sons, Ltd.